Nematode resistance to five anthelmintic classes in naturally infected sheep herds in Northeastern Brazil - Flávia da Silva,Francisca (2018)
Abstract This study aimed to evaluate the occurrence of nematode resistance to anthelmintics on sheep herds from the semi-arid region of Paraíba, Northeastern Brazil. Fecal Egg Count Reduction Test (FECRT) was carried out on 20 properties. In each herd, 30 animals were divided into five groups containing six animals each: group I, treated with albendazole 10%, 4 mg/kg; group II, ivermectin 0.08%, 0.2 mg/kg; group III, closantel 10%, 10 mg/kg; group IV, levamisole hydrochloride 5%, 5 mg/kg; and group V, monepantel 2.5%, 2.5 mg/kg. All treatments were administered orally as a single dose. Fecal samples were collected on days zero and 10 after treatment, to perform FECRT and coprocultures. Multiresistance was observed in all the properties; 95% had high resistance to albendazole, 85% to ivermectin, 80% to closantel, 40% to levamisole, and 45% to monepantel. On property 15, where monepantel was ineffective, a second FECRT for this anthelmintic was carried out 4 months after the first, resulting in 75% efficacy. Immediately after the FECRT result, two ewes were euthanized and necropsied, and Haemonchus contortus, Trichostrongylus axei, Trichostrongylus colubriformis, Oesophagostomum columbianum, and Trichuris ovis were recovered. It was concluded that the resistance of sheep gastrointestinal nematodes to antthelmintic, including monepantel, is high.